2017
DOI: 10.1071/cp17115
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of seed production and its association with forage production and agronomic traits in orchardgrass (Dactylis glomerata) under different moisture conditions

Abstract: Genetic analysis of seed production and the effect of water stress on seed and forage production have not been addressed simultaneously in orchardgrass (Dactylis glomerata L.). Thirty-six genotypes of orchardgrass were clonally propagated and evaluated in the field under two moisture environments (normal and water stress) during 3 years (2013–15). A high degree of variation was observed among genotypes for all of the measured traits. Water stress had a negative effect on seed weight per plant and dry matter bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…Moreover, higher estimates for PCV and GCV under the de cit irrigation regime compared with normal irrigation indicate that water de cit have increased genetic variation for most of the studied traits and therefore, selection under de cit irrigation would be more effective. Our ndings in this case are consistent with the reports of Abtahi et al [41] and Saeidnia et al [42]. However, some researchers stated that the genetic advance through selection is higher under normal irrigation [39,43].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, higher estimates for PCV and GCV under the de cit irrigation regime compared with normal irrigation indicate that water de cit have increased genetic variation for most of the studied traits and therefore, selection under de cit irrigation would be more effective. Our ndings in this case are consistent with the reports of Abtahi et al [41] and Saeidnia et al [42]. However, some researchers stated that the genetic advance through selection is higher under normal irrigation [39,43].…”
Section: Discussionsupporting
confidence: 93%
“…However, seed yield is particularly important for commercial breeding of many forage grasses and has received increasing attention (Boelt & Studer, 2010; Statkevičiūtė, Aleliūnas, Kemešytė, & Brazauskas, 2016). Moreover, in some regions of the world like Iran, forage grasses are usually used for seed production in the first harvest and hay production or pasture in subsequent harvests (Saeidnia, Majidi, & Mirlohi, 2017a, 2018). Due to production and environmental reasons, more attention should be paid to defoliation managements such as seed and forage management (Dowling et al., 2006; Kemp, Michalk, & Virgona, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some researchers reported that genetic gain through selection is usually higher under normal irrigation than de cit irrigation [39,41]. However, other researchers have also reported that the genetic advance through selection was higher under de cit irrigation [42,43]. Moderate to high heritability estimates observed for all of the evaluated traits indicates that the improvement of these traits would be possible through selection and also emphasizes that detecting of marker-trait associations is possible for these traits [44].…”
Section: Discussionmentioning
confidence: 95%